Introduction to the Special Issue: Rise of the “Knowledge Structure”: Implications for the Exercise of Power in the Global Political Economy - Haggart, Blayne (Journal of information policy (University Park, Pa.), 2017)
Somewhat paradoxically, the implications of knowledge governance's changing role for the exercise of power in the Information Age remains underappreciated outside those scholars and policymakers directly engaged with these specific areas. This special issue brings together political scientists and communication scholars to consider the issue of knowledge governance through the theoretical framework of Susan Strange. This introduction examines the treatment of knowledge-governance issues within the mainstream of International Political Economy scholarship and briefly contextualizes the contribution of each article in this special issue.